Tectonic control of accommodation space and sediment supply within the Mata Amarilla Formation (lower Upper Cretaceous) Patagonia, Argentina - Varela, Augusto Nicolás (2015)
The Mata Amarilla Formation dates from the early Upper Cretaceous and was deposited during a transition in tectonic regime from the extensional Rocas Verdes Basin to the Austral Foreland Basin. Detailed sedimentological logs and architectural parameters were used to define 13 facies associations. The distribution of facies associations and associated variations in fluvial architecture have enabled large-scale changes in accommodation space/sediment supply ratios (A/S ratio) to be defined for the three component sections of the Mata Amarilla Formation. The lower and upper sections are characterized by a high A/S ratio, whereas the middle section corresponds to a low A/S ratio. In the western part of the study area, small-scale variations in the A/S ratio were recognized in the middle section. The strong west to east trend in evolution of the fluvial systems coincides with the direction of propagation of the Patagonian fold and thrust belt, which is located to the west of the study area. Intervals of high A/S ratio (i.e. lower and upper sections) are interpreted to have developed during periods of increased loading by the fold and thrust belt caused by tectonic uplift. In contrast, intervals of low A/S ratio (i.e. middle section) were developed during periods of tectonic quiescence. This article suggests that the large-scale variations in A/S ratios are related to different rates of migration and growth of the Patagonian fold and thrust belt, whereas the small-scale variation occurred in response to specific periods of thrusting and folding in the Patagonian fold and thrust belt (i.e. local loads). This field example of the effects of different scales of variation in A/S ratios across the Austral Foreland Basin could be used to recognize similar tectonically forced variations in stratigraphic architecture in other foreland basins throughout the world, as well as to understand the response of fluvial systems to such changes.